Analisis kurikulum dan sistem pembelajaran di MIN 3 Banyuwangi - A’yunin, Azza Nuraida Qurrota (Maliki Interdisciplinary Journal, 2024)
The Frequent changes in the Minister of Education have an impact on the education curriculum in Indonesia. The current curriculum is not far from the combination and evaluation of the previous curriculum up to the current 2013 curriculum. As a result of these curriculum changes, learning at Madrasah Ibtidaiyah Negeri 3 Banyuwangi takes the form of vision, mission, objectives, methods, media, learning resources, learning approaches, as well as evaluation of learning and the curriculum used. This research uses descriptive qualitative research. Data collection techniques use interview, observation and documentation techniques. The results of his research are a link between the vision, mission and goals at Madrasah Ibtidaiyah Negeri 3 Banyuwangi with the 2013 curriculum currently being implemented by the government.